The Predatory Mites (Phytoseiidae, Parasitiformes) in the Fauna of Ukraine: a New Species and a New Subgenus of the Genus Graminaseius - Kolodochka, L. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
The predatory mites of the genus Graminaseius Chant & McMurtry, 2004 (Phytoseiidae, Parasitiformes) of the Ukrainian fauna are reviewed. Information on the species of the genus previously known from Ukraine is summarized and supplemented. Alustoseius Kolodochka, subgen. n. (type species: Amblyseius alustoni Livschitz & Kuznetzov, 1972) is established to include Graminaseius (Alustoseius) altimontanus Kolodochka, sp. n. described based on a female collected in the Crimean Mountains, and Graminaseius (Alustoseius) alustoni (Livschitz et Kuznetzov, 1972), comb. n. previously assigned to Amblyseius and Neoseiulus. Two species are added one the list, one of which, Graminaseius (s. str.) lituatus (Athias-Henriot, 1961), comb. n. was previously assigned to Amblyseius and Typhlodromips, is recorded from Ukraine for the first time. All the species are redescribed and illustrated based on the study of exhausting material, with diagnoses, depositaries of type material, distribution in Ukraine and world, types of habitats, as well as a key to subgenera and species occurring in Ukraine are provided.